Emerging Trends and Research Foci in Tumor Microenvironment of Pancreatic Cancer: A Bibliometric and Visualized Study - Wu, Kaiwen; Liu, Ye; Liu, Lei; Peng, Yunlan; Pang, Honglin; Sun, Xiaobin; Xia, Demeng (Frontiers in Oncology, 2022)
Background: Pancreatic cancer (PC) is a serious disease with high mortality. The tumor microenvironment plays a key role in the occurrence and development of PC. The purpose of this study is to analyze trends by year, country, institution, journal, reference and keywords in publications on the PC microenvironment and to predict future research hotspots. Methods: The Web of Science Core Collection was used to search for publications. We analyzed the contributions of various countries/regions, institutes, and authors and identified research hotspots and promising future trends using the CiteSpace and VOSviewer programs. We also summarized relevant completed clinical trials. Results: A total of 2155 papers on the PC microenvironment published between 2011 and 2021 were included in the study. Publications increase every year. The average number of citations per article was 32.69. The USA had the most publications, followed by China, and a total of 50 influential articles were identified through cocitation analysis. Clustering analysis revealed three clusters of keywords: carcinogenesis of PC, stroma of PC, and therapy of PC. Conclusion: The number of publications and research interest generally increased, and the USA has made prominent contributions to the study of the tumor microenvironment of PC. The current research hotspots mainly include cancer-associated fibroblasts, extracellular vesicles and pancreatic cancer treatment, which might be future research directions.